Goiânia-GO : um projeto de cidade jardim que não resistiu à força do progresso e do capital imobiliário : 1930-2010 - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Understanding how the city connects with the environmental where is located and all the interferences in this environmental, could help to comprehend socialcultural factors of our history, wich is indispensable reflection for the social-environmental cities planning. In this perspective, the present study aims to show that the Goiânia construction project, designed by Atílio Correia Lima, based on the principles of a sustainable city that wasinspired by the architectural style of garden cities of Ebenezer Howard. The future capital of the State of Goiás was designed with the goal of keeping the balance between nature, society and the economy to ensure the quality of life for future residents with ample spaces for squares, gardens and recreational areas. However, the Goiânia´s history shows that planning succumbed to the improvise. The Public Power due to increasing economic demand, demographic and social after 1950 failed to maintain the originality of the traces that ensured maintenance and the preservation of green áreas, wich have been occupied, donated and legalized with the connivance of the State and Municipal Government.
Keywords: Goiânia; Sustentabilidade; Desenvolvimento; Urbanização; Goiânia; Sustainability; Development; Urbanization; OUTROS; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL